2015
DOI: 10.1111/pme.12884
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Subjective Effects with Systemic Opioid Exposure from Fixed-Dose Combinations of Oxycodone/Acetaminophen in Recreational Users of Prescription Drugs

Abstract: Immediate-release/extended-release oxycodone/acetaminophen produced lower oxycodone C and longer t than immediate-release oxycodone/acetaminophen. Lower oxycodone concentrations, particularly at earlier time points, were strongly correlated with lesser positive subjective drug effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…300 ng/mL was correlated with the subjective perception of feeling high. [13] Thus, in order to judge whether our vaccines could generate a robust antibody response to effectively block this concentration, serum from mice vaccinated with Oxy-TT and Hydro-TT were challenged with 300 ng/mL of oxycodone and hydrocodone. The amount of drug able to diffuse across a dialysis membrane was then quantified by LCMS.…”
mentioning
confidence: 99%
“…300 ng/mL was correlated with the subjective perception of feeling high. [13] Thus, in order to judge whether our vaccines could generate a robust antibody response to effectively block this concentration, serum from mice vaccinated with Oxy-TT and Hydro-TT were challenged with 300 ng/mL of oxycodone and hydrocodone. The amount of drug able to diffuse across a dialysis membrane was then quantified by LCMS.…”
mentioning
confidence: 99%
“…For example, strong correlations were established between oxycodone C max and maximum VAS for Drug Liking in recreational opioid users following a single dose of immediate-release/extended-release oxycodone/acetaminophen in an intact or manipulated condition. 5 Several studies reported that the abuse potential of opioids are correlated with the rate of rise of drug plasma concentration. [6] , [7] , [8] , [9] However, concerns remain for unraveling the relationships between PK exposure and clinical abuse potential scores and claims have been made such relationships may be complex and inconsistent considering the subjective nature of PD measures and the wide range of AD technologies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, strong correlations were established between oxycodone C max and maximum VAS for Drug Liking in recreational opioid users following a single dose of immediate-release/extended-release oxycodone/acetaminophen in an intact or manipulated condition. 5 Several studies reported that the abuse potential of opioids are correlated with the rate of rise of drug plasma concentration. 6À9 However, concerns remain for unraveling the…”
Section: Introductionmentioning
confidence: 99%
“…In a study evaluating the effects of exposure to fixed-dose combinations of oxycodone and acetaminophen in nondependent, recreational opioid users, a lower oxycodone concentration was correlated with less positive subjective drug effects when examined at the aggregate level (ie, using mean PK vs mean PD data). 2 The rate of rise in plasma drug concentration is another PK parameter that has been related to attractiveness for abuse, with higher peak concentration over a shorter time related to greater abuse potential. 3,4 Support for this relationship has been demonstrated in studies of opioids, sedatives, and methylphenidate.…”
mentioning
confidence: 99%
“…Rapid absorption and rapid onset of action of opioids have been associated with greater abuse potential; however, few studies have evaluated the relationship between pharmacokinetic (PK) and pharmacodynamic (PD; eg, drug liking) parameters in subjects receiving opioids. In a study evaluating the effects of exposure to fixed‐dose combinations of oxycodone and acetaminophen in nondependent, recreational opioid users, a lower oxycodone concentration was correlated with less positive subjective drug effects when examined at the aggregate level (ie, using mean PK vs mean PD data) . The rate of rise in plasma drug concentration is another PK parameter that has been related to attractiveness for abuse, with higher peak concentration over a shorter time related to greater abuse potential .…”
mentioning
confidence: 99%